2020
DOI: 10.1109/toh.2020.2985962
|View full text |Cite
|
Sign up to set email alerts
|

Closed-loop Control using Electrotactile Feedback Encoded in Frequency and Pulse Width

Abstract: Sensory substitution by electrotactile stimulation has been widely investigated for improving the functionality of human-machine interfaces. Few studies, however, have objectively compared different ways in which such systems can be implemented. In this study, we compare encoding of a feedback variable in stimulation pulse width or stimulation frequency during a closed-loop control task. Specifically, participants were asked to track a predefined pseudorandom trajectory using a joystick with electrotactile fee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 40 publications
1
21
0
Order By: Relevance
“…Closed-loop control with electrotactile stimulation was assessed in several studies [19]- [24] but they focused on characterizing performance without estimating the model of the human controller. To the best of our knowledge, just two studies reported the human transfer functions when using electrotactile feedback; however, only for position control mode, showing that the transfer functions resembled low-pass filters [25], [26]. The findings for tactile feedback are so far in agreement with the theory of human manual control, but as described above, the assessment was overall scarce.…”
mentioning
confidence: 68%
See 1 more Smart Citation
“…Closed-loop control with electrotactile stimulation was assessed in several studies [19]- [24] but they focused on characterizing performance without estimating the model of the human controller. To the best of our knowledge, just two studies reported the human transfer functions when using electrotactile feedback; however, only for position control mode, showing that the transfer functions resembled low-pass filters [25], [26]. The findings for tactile feedback are so far in agreement with the theory of human manual control, but as described above, the assessment was overall scarce.…”
mentioning
confidence: 68%
“…We assessed the performance and estimated the model of the human controller in both control modes (position versus velocity) when the feedback was delivered using encoding in stimulation frequency. While most previous studies employed amplitude modulation (e.g., [19]- [22]), frequency modulation was selected since we have shown that it enables superior performance in the same type of closed-loop control task as used in this study [26]. Our a priori expectation was that a human controller adapts to different plant dynamics using electrotactile feedback in the same way it adapts when the feedback is transmitted visually.…”
mentioning
confidence: 99%
“…This experiment demonstrated that the average latency increases significantly with the network load. A closed-loop compensatory tracking task is performed in the closed-loop control using tactile input in [25], where the feedback is encoded to the user using frequency and amplitude modulation schemes. Significant time delay on the order of several hundred milliseconds has been noticed in this experiment.…”
Section: Related Workmentioning
confidence: 99%
“…where T r denotes the time elapsed in compressing the raw sensing data with compression ratio Q (see ( 19)), T f tx denotes the time elapsed in transmitting the compressed data (see ( 10)), T f d denotes the delay incurred in decompressing the compressed sensing data (see (25)), and T f c denotes the time elapsed in processing the sensing data (see ( 17)). T pf tx is the time elapsed in transmitting the low-level command (having number of packets N p f ) extracted from sensing data to the HO (see (10)).…”
Section: A Case 1: Data Compression At Robotmentioning
confidence: 99%
“…Closed-loop Control using Electrotactile Feedback Encoded in Frequency and Pulse Width. Dideriksen, J.L., +, TOH Oct.-Dec. 2020 Xu, H., +, TOH July-Sept. 2020 483-492…”
Section: Frequency Modulationmentioning
confidence: 99%